PENGARUH MUSIK KARYA BACH TERHADAP FUNGSI KOGNISI: ATENSI DAN MEMORI JANGKA PENDEK - Yenni Limyati; Azalia Rahmanita Erman; Winda Permata Sari; Johan Lucianus; Budi Widyarto Lana (NEURONA, 2018)
THE EFFECT OF MUSIC BACH’S WORKS ON COGNITION FUNCTION: ATTENTION AND SHORT-TERM MEMORYABSTRACTIntroduction: A student who has a myriad of activities on and off campus, besides being required to have the ability to manage time efficiently, they are also required to have a good cognitive function, especially for academic activities. Many factors can interfere with learning activities, including attention problems and difficulty remembering. Some studies say that Bach’s rhythmic and soft music influences the ability to absorb information and remember.Aims: Knowing the effect of listening to Bach’s music on attention and short-term memory.Methods: The study design was experimented with pre- and post-test designs. This research  was conducted on 30 student choir members who met the research criteria. The measured data are the time needed to write the Stroop test correctly and the number of words that can be remembered from the memory recall test before and after listening to Bach’s music “Largo Ma Non Tanto”. Statistical analysis used paired parametric t test and Wilcoxon nonparametric test with a significance limit of 5% (p<0.05).Results: The average Stroop test was faster in the post-test (17.56±3.82 seconds) than at the pre-test (20.25±3.66 seconds), with a p value <0.01 and the average recall memory test at at the post-test (14.13±1.43), compared to the pre-test (11.93±2.30), with p<0.01.Discussion: Bach’s “Largo Ma Non Tanto” improves attention and short-term memory.Keywords: Attention, short-term memory, Bach, tempoABSTRAKPendahuluan: Seorang mahasiswa yang memiliki segudang kegiatan di dalam maupun di luar kampus, selain dituntut memiliki kemampuan mengatur waktu yang efisien, mereka dituntut pula memiliki fungsi kognisi yang baik terutama untuk kegiatan akademis. Banyak faktor dapat mengganggu kegiatan pembelajaran, diantaranya gangguan atensi dan sulit mengingat. Beberapa penelitian mengatakan bahwa musik karya Bach yang ritmis dan lembut berpengaruh pada kemampuan menyerap informasi dan mengingat.Tujuan: Mengetahui pengaruh mendengarkan musik karya Bach terhadap atensi dan memori jangka pendek.Metode: Desain penelitian adalah eksperimental dengan rancangan pre- dan post-test. Penelitian ini dilakukan pada30 anggota paduan suara mahasiswa yang memenuhi kriteria penelitian. Data yang diukur yaitu waktu yang dibutuhkan untuk menulis dengan tepat tes Stroop dan jumlah kata yang dapat diingat dari tes recall memory sebelum dan sesudah mendengarkan musik Bach “Largo Ma Non Tanto”. Analisis statistik menggunakan uji parametrik t berpasangan dan uji non-parametrik Wilcoxon dengan batas kemaknaan α=5% (p<0,05).Hasil: Rerata tes Stroop lebih cepat pada saat post-test (17,56±3,82detik) dibanding saat pre-test (20,25±3,66 detik), dengan nilai p<0,01 dan rerata tes recall memory lebih besar pada saat post-test (14,13±1,43), dibanding saat pre-test (11,93±2,30), dengan p<0,01.Diskusi: Musik karya Bach “Largo Ma Non Tanto” meningkatkan atensi dan memori jangka pendek.Kata kunci: Atensi, memori jangka pendek, musik karya Bach, tempo